Pengaruh Minat Belajar Terhadap Hasil Belajar Peserta Didik Melalui Penerapan Model Inkuiri Terbimbing Berbantuan Simulasi PhET Pada Materi Gerak Harmonik Sederhana - Maria Avila; Oktavianus Ama Ki`i; Maria Ursula Jawa Mukin (Program Studi Pendidikan Fisika Universitas Katolik Widya Mandira, 2024)
The problem that is often faced is that many students are less interested and less motivated in learning physics, especially on the concept of simple harmonic motion. This has a negative impact on their learning outcomes, as indicated by low test scores and overall academic achievement. Therefore, an intervention is needed that can improve students' interest in learning and learning outcomes. This study aims to determine the interest and learning outcomes of physics students in class X IPA 6 SMA Negeri 2 Kupang in the guided inquiry learning model assisted by PhET simulation on simple harmonic motion material. This research is a descriptive quantitative study with a simple regression approach that aims to determine the effect between the variable of interest in learning on the variable of learning outcomes. The results of descriptive test analysis for interest variables and learning outcomes showed that the average percentage of interest in learning on pretest was 61% (high category) and on posttest was 72% (very high category); the average percentage of learning outcomes on pretest was 22 (low category) and on posttest was 86 (very high category). The regression test results show a significant effect of learning interest on student learning outcomes on simple harmonic motion material in guided inquiry learning assisted by PhET simulation. The application of guided inquiry learning model assisted by PhET simulation can increase students' learning interest, which in turn significantly improves their learning outcomes on simple harmonic motion material.